The Influence of the Gross Regional Domestic Product of the Trade and Manufacturing Industry and Services Sector on the Amount of Labor Absorption in the City of Samarinda and the City of Balikpapan - Felicx Simanjuntak; Rahcmad Budi Suharto; Diana Lestari; Akbar Lufi Zulfikar (International Journal of Management Research and Economics, 2025)
The purpose of this study was to determine the effect of the Gross Regional Domestic Product of the Trade and Processing Industry Sectors and Services on the Amount of Labor Absorption in Samarinda City and Balikpapan City. This study uses panel data from 2013 – 2022 in the two cities of Samarinda and Balikapapan using secondary data. Data analysis used a dummy variable multiple linear regression model using SPSS (Statistical Program Social Science) version 23. The results of this study indicate that the GRDP variables in the trade, manufacturing and service sectors together have a significant effect on the amount of labor absorption. The Trade Sector Variable partially has a significant positive effect on Total Labor Absorption. The Processing Industry Sector Variable partially has no significant effect on Total Labor Absorption. And the Service Sector Variable partially has a significant negative effect on Total Labor Absorption.